Information Content Assessment of the Federal Budget and the Budget Process in the Russian Federation - O. V. Morozov; M. A. Vasiliev (Статистика и экономика)
This article is devoted to the results of a statistical study of the composition of federal budget expenditures (the object of the study) from the standpoint of assessing its information content (the subject of the study). In the opinion of its authors, the issues of information content of budget decisions remain out of due attention not only from the participants of the budget process, but also in the practice of public administration in general. Therefore, the purpose of this study is to form scientifically based tools for assessing the information content, determining its quantitative indicators, clarifying the nature, hidden features and balance in the distribution of federal budget expenditures.Materials and methods. The analysis of the composition parameters of federal budget expenditures was carried out on the basis of statistical data of the Federal Treasury for 2014-2020. The theoretical foundations and research methods are developed based on the authors’ preferences regarding the results of conceptual and applied developments of domestic scientists in the field of synergetic information theory, structural analysis of systems, and modular theory of society. Quantitative methods of processing the initial data, tabular and graphical methods of visualizing the results of the study were used. Standard Microsoft Office application software packages were used to solve the research tasks.Results. Indexes of information content of the multicomponent systems’ composition and algorithms for their calculations are formed. Quantitative criteria are determined and a model for optimizing the composition of federal budget expenditures is presented. The comparison of actual and model indexes of the information content is presented as a way to adjust priorities in the composition of federal budget expenditures; as a way to develop tactics and strategies for the transition from the actual parameters of the expenditures’ composition to the “best” distribution, which is described by a quantitative model of the optimal combination of the scales of its components. Retrospective optimization options based on the results of the execution of expenditures in 2020 and promising options for optimizing the distribution of federal budget expenditures in 2022-2024 have been established.Conclusion. Assessment of the information content and optimization of the components’ scale of the budget expenditures’ composition are recognized as elements of management of the distribution of public resources in the budget process, ways to ensure control over the effectiveness of budget decisions and can be useful for participants in the budget process both at the stage of formation and at the stage of execution of budget expenditures.